Selective functionalization of complex heterocycles via an automated strong base screening platform. Issue 4 (22nd May 2017) - Boga, Sobhana Babu; Christensen, Melodie; Perrotto, Nicholas; Krska, Shane W.; Dreher, Spencer; Tudge, Matthew T.; Ashley, Eric R.; Poirier, Marc; Reibarkh, Mikhail; Liu, Yong; Streckfuss, Eric; Campeau, Louis-Charles; et al.
Abstract : An automated high throughput screening approach to optimizing strong base-mediated metalations. Abstract : Knochel–Hauser bases, derived from 2, 2, 6, 6-tetramethylpiperidinyl (TMP) metal amides, offer exceptional selectivity and functional group tolerance in the regioselective metalation of arenes and heteroarenes. The selectivity, stability and yield of these reactions are highly dependent on the nature of the base, additive and deprotonation temperature. We have developed and validated an automated micro-scale high throughput experimentation (HTE) approach to rapidly optimize base and temperature matrices. We describe the application of this approach to the regioselective functionalization of a variety of complex heterocycles and extension to the preparation of organometallic reagents for transition metal catalyzed cross-coupling screens.